Correlations between objective response rate and survival-based endpoints in first-line advanced non-small cell lung Cancer: A systematic review and meta-analysis. (August 2022) - Goring, Sarah; Varol, Nebibe; Waser, Nathalie; Popoff, Evan; Lozano-Ortega, Greta; Lee, Adam; Yuan, Yong; Eccles, Laura; Tran, Phuong; Penrod, John R.
Highlights: Objective response rate (ORR) was statistically associated with overall survival (OS) in a trial-level meta-analysis. The trial-level relationship between OS and ORR was stronger in immunotherapy-based compared to chemotherapy-only trials. For a given ORR benefit, OS gains were significantly larger with immunotherapy-based compared to chemotherapy-only trials. Abstract: Introduction: The study objective was to estimate the relationship between objective response and survival-based endpoints by drug class, in first-line advanced non-small cell lung cancer (aNSCLC). Materials and methods: A systematic literature review identified randomized controlled trials (RCTs) of first-line aNSCLC therapies reporting overall survival (OS), progression-free survival (PFS), and/or objective response rate (ORR). Trial-level and arm-level linear regression models were fit, accounting for inclusion of immunotherapy (IO)-based or chemotherapy-only RCT arms. Weighted least squares-based R 2 were calculated along with 95% confidence intervals (CIs). For the main trial-level analysis of OS vs. ORR, the surrogate threshold effect was estimated. Exploratory analyses involved further stratification by: IO monotherapy vs. chemotherapy, dual-IO therapy vs. chemotherapy, and IO + chemotherapy vs. chemotherapy. Results: From 17, 040 records, 57 RCTs were included. In the main analysis, trial-level associations between OS and ORR were statistically significant in both the IO-based and chemotherapy-only strata, with R 2 estimates of 0.54 (95% CI: 0.26–0.81) and 0.34 (0.05–0.63), respectively. OS gains associated with a given ORR benefit were statistically significantly larger within IO vs. chemotherapy comparisons compared to chemotherapy vs. chemotherapy comparisons (p < 0.001). Exploratory analysis suggested a trend by IO type: for a given change in ORR, 'pure' IO (IO monotherapy and dual-IO) vs. chemotherapy RCTs tended to have a larger OS benefit than IO + chemotherapy vs. chemotherapy RCTs. For ORR vs. PFS, trial-level correlations were strong in the IO-based vs. chemotherapy (R 2  = 0.84; 0.72–0.95), and chemotherapy vs. chemotherapy strata (R 2  = 0.69; 0.49–0.88). For OS vs. PFS, correlations were moderate in both strata (R 2  = 0.49; 0.20–0.78 and R 2  = 0.49; 0.23–0.76). Conclusion: The larger OS benefit per unit of ORR benefit in IO-based RCTs compared to chemotherapy-only RCTs provides an important addition to the established knowledge regarding the durability and depth of response in IO-based treatments.